The Role of Ethylene in Seed Dormancy with Particular Reference to Apple (Malus doniestica Bork H.) Seeds - Keong, Wan.Chee (1980)
The involvement of ethylene in the regulation of apple seed dormancy and germination was investigated. No relationship could be established between the rate of endogenous ethylene biosynthesis by seeds and their ability to germinate. Addition of ethephon (2-chloroethylphosphonic acid) to the stratification medium promoted ethylene production by seeds, but had no consistent effect on germination. The presumed inhibitor of ethylene action or synthesis, 8-hydroxyquinoline sulfate and silver nitrate, reduced ethylene production but did not inhibit germination at non-toxic levels. It is concluded that ethylene is not essential for breaking dormancy in apple seeds, nor is germination an ethylene-induced response.